Social networking - Orr, Tamra (Global citizens: social media., 2019)
Provides a history of social networking from the origin of the internet through modern social media sites. Examines the etiquette and ethics of social networking and how companies use networking for their business. Includes color photographs, sidebars with critical thinking questions, and sources for further learning.